Activities of MASPENA - Slutan, Donny (Universiti Teknologi MARA, Sarawak, 2015)
The page highlights key activities organized by MASPENA, including the 7th Annual General Meeting (AGM), student elections, independence festival, academic clinics (ECO162, MGT162 and ACC106), Malaysian politics (PAD310) forum and Ramah Tamah Aidilfitri and Persidangan Mahasiswa Fakulti Sains Pentadbiran & Pengajian Polisi UiTM Se-Malaysia kali ke-6. It showcase student participation, events held at UiTM Samarahan, and efforts to welcome new members while promoting cultural and academic engagement.